"I Shot the Sheriff": Irony, Sarcasm and the Changing Nature of Workplace Resistance. (3rd September 2018) - Alcadipani, Rafael; Hassard, John; Islam, Gazi
Abstract: The spread of Lean management has fuelled debates over the changing nature of workplace domination. While Lean discourses often espouse a 'human relations' approach, research has suggested the proliferation of coercion systems and questioned whether Lean is instead shorthand for cost‐cutting and new forms of domination. The varied interpretations of Lean have explained the heterogeneity of worker responses, including forms of resistance. Our ethnography explores this heterogeneity by examining the implementation of Lean in a printing factory and tracing the emergence of shopfloor opposition. Various tactics were devised by workers, ranging from tangible procedures such as sabotage and working‐to‐rule to more subtle forms reflecting irony and contempt. We argue that the distinctive manifestations of domination emerging during the Lean programme stimulated particular forms of worker reaction, which are explained through fieldwork illustrations. Overall, we produce a theoretical explanation of domination and resistance that builds upon and extends the extant scholarship.